Conference Review: The 2nd Annual Seminar of Experimental Archaeology in Norway - Lotte Eigeland (EXARC Journal)
Twenty-seven participants gathered at Hringariki museum at Hønefoss in Eastern Norway during a two-day conference from September 1st thru 2nd, 2012. Day 1 was divided into two parts. The first consisted of lectures with sufficient time set apart for questions after each talk. The second part of the day consisted of a round table discussion dealing with the agenda of Norsk Forum for EksperimentellArkeologi [the Norwegian Forum for Experimental Archaeology].